Masyarakat Modern dan Kenakalan Remaja: Suatu Telaah Sosial - Khairi, Ahmad Imam (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
This study tried to assess the problem of juvenile delinquency that lately rife in society. Delinquency is conducted diverse, ranging from the mild to the delinquency that led to the criminal delinquency. Even more worrying is the increasing numbers of teenagers who went to prison for his actions that lead to crime, from drugs, murder, and teenage prostitutes. This research uses a qualitative approach. Collecting data in this study derived from statistical data regarding juvenile delinquency contained in East Java, where the data is contained in adolescents aged 21 years and below the Prisoners, but it is also supported by the literature that supports the research. From the data found in 2015, the number of child convicts at the end of the year reached 127 people, then increased at the end of 2016 to 137 child prisoners, at the end of 2017 experienced a significant increase reaching 195 prisoners, then at the end of 2018 and 2019 decreased by 186 and 143 child convicts, respectively, with cases dominated by drug abuse as much as 51 percent where drug users and addicts are still children or adolescents under 19 years. Followed by cases of prostitution, gangsters, ect. The cause of juvenile delinquency can be caused by various factors, other than self-defense of the weak and family factors. Delinquency also be due to lack of ability of adjustment to the social environment, westernization, economic problems, and a basic lack of faith and religious values as a bastion of self.